The advertisement call and geographic distribution of Odontophrynus lavillai Cei, 1985 (Anura: Odontophrynidae) - Rosset, Sergio Daniel (2014)
Currently, the genus Odontophrynus Reinhardt & Lütken comprises 11 species distributed in southern and eastern South America. Among them, O. americanus (Duméril & Bibron), O. lavillai Cei, O. cordobae Martino & Sinsch, and O. maisuma Rosset constitute a group of sibling diploid and tetraploid species, the O. americanus group (Rosset et al. 2006 and literature cited therein).